Multi‐system involvement in a severe variant of fibrodysplasia ossificans progressiva (ACVR1 c.772G>A; R258G): A report of two patients. (11th June 2015) - Kaplan, Frederick S.; Kobori, Joyce A.; Orellana, Carmen; Calvo, Inmaculada; Rosello, Monica; Martinez, Francisco; Lopez, Berta; Xu, Meiqi; Pignolo, Robert J.; Shore, Eileen M.; Groppe, Jay C.
Abstract : Severe variants of fibrodysplasia ossificans progressiva (FOP) affect <2% of all FOP patients worldwide, but provide an unprecedented opportunity to probe the phenotype–genotype relationships that propel the pathology of this disabling disease. We evaluated two unrelated children who had severe reduction deficits of the hands and feet with absence of nails, progressive heterotopic ossification, hypoplasia of the brain stem, motor and cognitive developmental delays, facial dysmorphology, small malformed teeth, and abnormal hair development. One child had sensorineural hearing loss, microcytic anemia, and a tethered spinal cord and the other had a patent ductus arteriosus and gonadal dysgenesis with sex reversal (karyotype 46, XY female). Both children had an identical mutation in ACVR1 c.772A>G; p.Arg258Gly (R258G), not previously described in FOP. Although many, if not most, FOP mutations directly perturb the structure of the GS regulatory subdomain and presumably the adjacent αC helix, substitution with glycine at R258 may directly alter the position of the helix in the kinase domain, eliminating a key aspect of the autoinhibitory mechanism intrinsic to the wild‐type ACVR1 kinase. The high fidelity phenotype–genotype relationship in these unrelated children with the most severe FOP phenotype reported to date suggests that the shared features are due to the dysregulated activity of the mutant kinase during development and postnatally, and provides vital insight into the structural biology and function of ACVR1 as well as the design of small molecule inhibitors. © 2015 Wiley Periodicals, Inc.